Investigation of morphology and compressive properties of diamond reinforced porous aluminium composites - Parveez, Bisma; Jamal, Nur Ayuni; Mohamed Saleem, Muhammad Raeez (ASIAN SCHOLARS NETWORK, 2023)
In the present work, porous aluminium composite with varying diamond particles content (4, 8, 12, and 16 wt. %) were developed via powder metallurgy technique. Porosity was attained by using 30 wt. % Polymethylmethacrylate particles as a space holder. The effects of varying content of diamond on the morphology, densities, porosities, compressive properties as well as energy absorption were studied. Morphology of the porous Al composite demonstrated the formation of closed- cell macro pores that were uniformly distributed within the Al matrix regardless of different content of diamond particles. However, increasing diamond content was found to alleviate un-wetting phenomenon between Al matrix and diamond particles leading to increased porosities from 34.8% to 26.2%. The compressive properties also declined however maximum values for plateau stress (7.50MPa) and energy absorption capacity 1.7(Mj/m3) were acquired at 8wt.% diamond content.